Polarizing element, polarizing plate, and image display device

CN117677873BActive Publication Date: 2026-11-03SUMITOMO CHEM CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280048989.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-15
Filing Date
2022-07-08
Publication Date
2026-11-03
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

现有的图像显示装置在高温环境下,偏振板的可见度修正单体透射率降低问题未能有效抑制。

Method used

A polarizing element with dichroic pigment adsorbed and oriented on a polyvinyl alcohol-based resin layer is designed to meet specific relationships by controlling the color distribution and boron content of the polarizing element. The layer is then cured using a water-based adhesive to form the interlayer filling structure of the image display device.

Benefits of technology

It effectively suppresses the reduction of the transmittance and polarization degree of the polarizing plate in high-temperature environments, maintains the visibility of the image display device, and prevents peeling between transparent components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117677873B_ABST
    Figure CN117677873B_ABST
Patent Text Reader

Abstract

Provided is a polarizing element that can suppress a decrease in visible light transmittance of a single cell even when the polarizing element is exposed to a high-temperature environment as a component of an image display device configured by filling layers, and a polarizing plate and an image display device. In the polarizing element, a dichroic dye is adsorbed and oriented in a polyvinyl alcohol-based resin layer. When a color strength of a region having the largest color strength among three regions divided by three equal parts in a thickness direction of the polarizing element is S1 and a color strength of a region having the smallest color strength is S2, the polarizing element satisfies the following formula (1): 0 ≤ S2 / S1 ≤ 0.95 (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polarizing element, a polarizing plate having a polarizing element, and an image display device having a polarizing plate. Background Technology

[0002] Liquid crystal displays (LCDs) are not only used in LCD televisions, but also widely used in personal computers, mobile devices such as mobile phones, and automotive applications such as navigation systems. Typically, an LCD device has a liquid crystal panel component formed by bonding polarizing plates to both sides of liquid crystal cells with adhesive. The display is achieved by controlling the light from a backlight component using the liquid crystal panel component. In recent years, organic electroluminescent (EL) displays have also been widely used in televisions, mobile devices such as mobile phones, and automotive applications such as navigation systems, similar to LCDs. In organic EL displays, to suppress the mirror-like effect caused by external light being reflected by the metal electrode (cathode), a circular polarizing plate (a laminate containing polarizing elements and a λ / 4 plate) is sometimes placed on the viewing side surface of the image display panel.

[0003] As mentioned above, polarizing plates are increasingly being used in vehicles as components of liquid crystal display devices and organic EL display devices. Polarizing plates used in automotive image display devices, compared to those used in mobile devices such as televisions and mobile phones (not automotive applications), are frequently exposed to high temperatures and require less change in properties at high temperatures (high-temperature durability).

[0004] In image display devices, to prevent damage to the image display panel from impacts from external surfaces, a front transparent plate (sometimes called a "window layer") such as a transparent resin plate or glass plate is sometimes provided on the viewing side relative to the polarizing plate of the image display panel. In image display devices equipped with a touch panel, a touch panel is sometimes provided on the viewing side relative to the polarizing plate of the image display panel, and a front transparent plate is provided on the viewing side relative to the touch panel.

[0005] In image display devices, if an air layer exists between the image display panel and transparent components such as a front transparent panel or touch panel, reflected glare from external light is generated due to light reflection at the interface with the air layer, tending to reduce the visibility of the image. Therefore, a structure is sometimes adopted in which the space between the polarizer constituting the viewing side surface of the image display panel and the transparent component is filled with a layer other than the air layer, usually a solid layer (hereinafter sometimes referred to as "interlayer filler"). It is preferable to use a material whose refractive index is close to that of the polarizer and / or the transparent component. As an interlayer filler, in order to suppress the reduction in visibility caused by light reflection at the interface with the air layer and to bond and fix the components together, an adhesive or a UV-curable adhesive (e.g., Patent Document 1) is used.

[0006] Image display devices with the interlayer filler structure described above are increasingly being used in mobile devices such as cell phones that are frequently used outdoors. Furthermore, due to the increasing demands for visibility in recent years, research is underway into using similar structures in automotive applications such as navigation devices, where a front transparent panel is disposed on the surface of the image display panel, and an adhesive layer is used to fill the space between the image display panel and the front transparent panel.

[0007] Patent Document 2 discloses that when an image display device having an interlayer filler is placed at a temperature of 95°C for, for example, 200 hours, a significant decrease in transmittance is observed in the central portion in the plane of the polarizing plate. However, if it is a single polarizing plate, no significant decrease in transmittance is observed even after being placed at a temperature of 95°C for 1000 hours. Based on these results, it can be considered that the significant decrease in transmittance of the polarizing plate at a temperature of 95°C in Patent Document 2 is a problem specific to image display devices configured to be exposed to a temperature of 95°C, namely, one side of the polarizing plate is bonded to the image display unit, and the other side is bonded to transparent components such as a touch panel or a front transparent plate.

[0008] Patent document 2 discloses that the water content per unit area of ​​the polarizing plate is set to a predetermined amount or less, and the saturated water absorption of the transparent protective film attached adjacent to the polarizing element is set to a predetermined amount or less, thereby suppressing the decrease in the transmittance of the polarizing plate in an environment with a temperature of 95°C.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent Application Publication No. 11-174417

[0012] Patent Document 2: Japanese Patent Application Publication No. 2014-102353 Summary of the Invention

[0013] The problem that the invention aims to solve

[0014] However, it was found that if the image display device with the above configuration is exposed to a high temperature environment of 115°C, it is not possible to sufficiently suppress the decrease in the transmittance of the polarizer's visibility correction element.

[0015] The object of the present invention is to provide a polarizing element that can effectively suppress the decrease in transmittance of the visibility correction element even when a component of an image display device consisting of an interlayer filling structure in which a solid layer and a polarizing plate are in contact on both sides is exposed to a high-temperature environment, and to provide a polarizing plate having a polarizing element and an image display device having a polarizing plate.

[0016] Methods for solving problems

[0017] The present invention provides the following polarizing element, polarizing plate, and image display device.

[0018] [1] A polarizing element, which is formed by the adsorption and orientation of dichroic pigments in a polyvinyl alcohol-based resin layer.

[0019] When the chromaticity of the region with the highest chromaticity among the three regions divided into three equal parts in the thickness direction by the above polarization element is set as S1, and the chromaticity of the region with the lowest chromaticity is set as S2, the following relationship (1) is satisfied.

[0020] 0≤S2 / S1≤0.95 (1)

[0021] [2] According to the polarization element described in [1], the region with the smallest staining degree among the three regions is the region located in the center in the thickness direction.

[0022] [3] The polarizing element described in [1] or [2], wherein the polarizing element comprises boron,

[0023] The boron content in the aforementioned polarization element is 4.0% by mass or more and 8.0% by mass or less.

[0024] [4] The polarizing element described in any one of [1] to [3], wherein the dichroic pigment is iodine.

[0025] (5) A polarizing plate having a polarizing element and a transparent protective film as described in any one of [1] to [4].

[0026] [6] The polarizing plate described in [5] further comprises an adhesive layer for bonding the polarizing element to the transparent protective film.

[0027] The adhesive layer described above is a layer obtained by curing a water-based adhesive.

[0028] [7] According to the polarizing plate described in [6], wherein the aforementioned aqueous adhesive contains methanol.

[0029] The methanol content in the above-mentioned water-based adhesive is 10% by mass or more and 70% by mass or less.

[0030] [8] The polarizing plate described in [6] or [7], wherein the above-mentioned water-based adhesive further comprises a polyvinyl alcohol resin.

[0031] [9] The polarizing plate according to any one of [6] to [8], wherein the thickness of the adhesive layer is 0.01 μm or more and 7 μm or less.

[0032]

[10] The polarizing plate according to any one of [5] to [9], wherein the polarizing plate is used in an image display device,

[0033] In the above-mentioned image display device, a solid layer is provided in contact with both sides of the polarizing plate.

[0034]

[11] An image display device having an image display unit, a first adhesive layer laminated on the observation side surface of the image display unit, and a polarizing plate described in any one of [5] to

[10] laminated on the observation side surface of the first adhesive layer.

[0035]

[12] The image display device described in

[11] further comprises a second adhesive layer laminated on the observation side surface of the polarizing plate and a transparent component laminated on the observation side surface of the second adhesive layer.

[0036]

[13] According to the image display device described in

[12] , the transparent component is a glass plate or a transparent resin plate.

[0037]

[14] According to the image display device described in

[12] , the transparent component is a touch panel.

[0038] Invention Effects

[0039] According to the present invention, a polarizing element can be provided that can effectively suppress the decrease in transmittance of the visibility correction monomer even when a component constituting an image display device with interlayer filling is exposed to a high-temperature environment, and a polarizing plate having the polarizing element and an image display device having the polarizing plate are provided. Attached Figure Description

[0040] Figure 1 This is a schematic cross-sectional view illustrating a polarization element according to one embodiment of the present invention.

[0041] Figure 2 This is a schematic cross-sectional view of a polarizing plate illustrating one embodiment of the present invention.

[0042] Figure 3 (a) and (b) are illustrative diagrams illustrating the steps used to determine staining degree.

[0043] Figure 4 This is an explanatory diagram used to illustrate the method of calculating the integrated intensity distribution from Raman spectra. Detailed Implementation

[0044] Hereinafter, preferred embodiments of the polarizing element, polarizing plate, and image display device will be described with reference to the accompanying drawings.

[0045] (Polarization element)

[0046] Figure 1 This is a schematic cross-sectional view illustrating the polarization element of this embodiment. The polarization element 1 is an absorption-type polarizing film that absorbs linearly polarized light having a vibration plane parallel to its absorption axis and transmits linearly polarized light having a vibration plane orthogonal to the absorption axis (parallel to the transmission axis).

[0047] Polarizing element 1 is a component formed by the adsorption and orientation of dichroic pigments on a polyvinyl alcohol-based resin layer (hereinafter sometimes referred to as "PVA-based resin layer"). Polarizing element 1 can be a single-layer polarizing layer formed by the adsorption and orientation of dichroic pigments on a PVA-based resin layer, or it can have a multilayer structure with two or more layers of the polarizing layer stacked on top of each other. In the case where polarizing element 1 has a multilayer structure, the two or more polarizing layers included in polarizing element 1 can be stacked via an adhesive layer.

[0048] For polarizing element 1, such as Figure 1 As shown, when the saturation degree of the region with the highest saturation degree among the three regions 11 to 13 divided into three equal parts by dividing the polarizing element 1 in the thickness direction 100 is set as S1, and the saturation degree of the region with the lowest saturation degree is set as S2, the following relationship (1) is satisfied.

[0049] 0≤S2 / S1≤0.95 (1)

[0050] like Figure 1 As shown, the three regions 11 to 13 of the polarization element 1 are regions arranged along the thickness direction 100 of the polarization element 1. Regions 11 and 13 are located on the surface side of the thickness direction 100 of the polarization element 1, and region 12 is located in the center of the thickness direction 100 of the polarization element 1.

[0051] In formula (1), S2 / S1 is preferably 0.90 or less, more preferably 0.85 or less, and even more preferably 0.75 or less. Alternatively, it can be 0.1 or more, or 0.3 or more.

[0052] By ensuring that polarizing element 1 satisfies the relationship in equation (1) above, the decrease in the transmittance Ty (hereinafter sometimes referred to as "transmittance Ty") of the visibility correction monomer can be effectively suppressed under high-temperature conditions. The reason for this can be considered as follows. It is speculated that the dichroic pigment contained in polarizing element 1 promotes the polyolefination reaction of the polyvinyl alcohol resin (hereinafter sometimes referred to as "PVA resin") constituting the PVA resin layer through dehydration. Since PVA resin is easily dehydrated under high-temperature conditions, polyolefination of PVA resin is more likely to occur, and the transmittance Ty of the polarizing element is more likely to decrease. It can be considered that the region with low staining intensity in polarizing element 1 indicates that the amount of dichroic pigment present in that region is small. Therefore, it is believed that by ensuring that polarizing element 1 has a region with low staining intensity in a manner that satisfies the relationship in equation (1) above, the polyolefination of PVA resin under high-temperature conditions can be effectively suppressed, and the decrease in the transmittance Ty of polarizing element 1 can be suppressed.

[0053] The so-called polyene formation of PVA-based resins refers to the formation of a polyene structure (-C=C)n- in the PVA-based resin constituting polarization element 1. For example, this can be achieved by using Raman spectroscopy of polarization element 1 to measure the polyene structure based on 1100 cm⁻¹. -1 Nearby (from =CC= key) and 1500cm -1 The presence of a peak in the vicinity (from the -C=C- bond) confirms this (Patent Document 2,

[0012] paragraph).

[0054] The polarization element 1 that satisfies the relationship of equation (1) can also suppress the reduction of visibility correction polarization degree Py (hereinafter sometimes referred to as "polarization degree Py") and hue ab in a high-temperature environment.

[0055] The region with a color intensity S1 (the region with the highest color intensity) can be any of regions 11 to 13, but is preferably at least one of regions 11 and 13 located on the surface of the polarizing element 1 in the thickness direction 100. The region with a color intensity S2 (the region with the lowest color intensity) can be any of regions 11 to 13, but is preferably region 12 located in the center of the polarizing element 1 in the thickness direction 100. Polyolefination of PVA-based resin is considered to easily occur from the central portion of the polarizing element 1 in the thickness direction 100. Therefore, it is conjectured that by making the region with a color intensity S2 the region 12 located in the center of the thickness direction 100, the polyolefination of the PVA-based resin constituting the polarizing element 1 can be effectively suppressed.

[0056] The staining degree can be determined using the steps [i] to [iv] below, and more specifically, using the method described in the examples described later. [i] Obtain Raman spectra for each measurement point set at a spacing of 1 μm along the thickness direction 100 of the polarizing element 1. [ii] Calculate the wavenumber 80 cm⁻¹ of the obtained Raman spectra.-1 ~180cm -1 [iii] Obtain the integral intensity distribution by plotting the calculated integral intensity relative to the thickness direction 100 of the polarizing element 1. [iv] In the obtained integral intensity distribution, calculate the integral area of ​​each of the three regions that are divided into three equal parts along the thickness direction 100 of the polarizing element 1, and set them as the chromaticity of each region.

[0057] Methods for obtaining polarizing element 1 that satisfies equation (1) include: preparing two or more polarizing layers with different dyeing degrees and stacking these polarizing layers via an adhesive layer; preparing a multilayer structure of a PVA-based resin layer having two or more layers with different polymerization degrees and saponification degrees of PVA-based resin, and using the PVA-based resin layer to manufacture polarizing element 1; and using a single-layer polarizing layer with different dyeing degrees in the thickness direction 100 as polarizing element 1. Methods for manufacturing a single-layer polarizing layer with different dyeing degrees in the thickness direction 100 include: adjusting at least one of the concentration of dichroic pigment, dyeing temperature, and dyeing time when dyeing the PVA-based resin layer with dichroic pigment in the polarizing layer manufacturing method described later; adjusting at least one of the boric acid concentration, temperature, and treatment time when treating the boric acid aqueous solution of the PVA-based resin layer adsorbed with dichroic pigment in the polarizing layer manufacturing method described later; manufacturing a polarizing layer using a laminated film with a substrate film disposed on one side of the PVA resin layer, and adjusting the treatment conditions of the laminated film (dyeing conditions, treatment conditions using boric acid aqueous solution, etc.).

[0058] The polarizing element 1 preferably contains boron. The boron content in the polarizing element 1 is preferably 4.0% by mass or more, more preferably 4.2% by mass or more, even more preferably 4.4% by mass or more, and preferably 8.0% by mass or less, more preferably 7.0% by mass or less, even more preferably 6.0% by mass or less. The boron content in the polarizing element 1 is the proportion of boron when the polarizing element 1 is set to 100% by mass, and can be determined using the method described in the embodiments described later. Boron in the polarizing element 1 is considered to exist in the form of boric acid or in a state where boric acid and the constituent elements of the PVA-based resin form a cross-linked structure; the boron content mentioned here is an amount measured in boron atoms (B). The boron content in the polarizing element 1 can be adjusted by adjusting the boron content contained in the polarizing layer described later.

[0059] It is speculated that by keeping the boron content in polarizing element 1 within the aforementioned range, polyolefin formation of the PVA-based resin is less likely to occur under high-temperature conditions. Therefore, it is believed that even when components constituting the interlayer filling structure of the image display device described later are exposed to high-temperature conditions, the decrease in the transmittance Ty of polarizing element 1 can be suppressed more effectively.

[0060] On the other hand, if the boron content in polarizing element 1 is greater than the above-mentioned range, the shrinkage force of polarizing element 1 will increase, which may easily lead to undesirable conditions such as peeling between it and other components, such as transparent parts, when assembled into an image display device. If the boron content in polarizing element 1 is less than the above-mentioned range, it will be difficult to obtain a polarizing element with the desired optical properties.

[0061] The polarizing element 1 preferably contains potassium. From the viewpoint of suppressing the degradation of the optical properties of the polarizing element 1 under high-temperature conditions, the potassium content in the polarizing element 1 is preferably 0.28% by mass or more, more preferably 0.32% by mass or more, and even more preferably 0.34% by mass or more. From the viewpoint of suppressing the color tone change of the polarizing element 1 under high-temperature conditions, the potassium content in the polarizing element 1 is preferably 0.60% by mass or less, more preferably 0.55% by mass or less, and even more preferably 0.50% by mass or less. The potassium content in the polarizing element 1 is the proportion of potassium contained when the polarizing element 1 is set to 100% by mass, and can be calculated, for example, as the mass percentage (mass%) of potassium relative to the mass of the polarizing element using high-frequency inductively coupled plasma (ICP) emission spectrophotometry. The potassium content in the polarizing element 1 can be adjusted by adjusting the potassium content contained in the polarizing layer, as described later.

[0062] When the boron and potassium contents in polarizing element 1 are within the ranges described above, there is a trend towards a higher boron content and a lower potassium content compared to conventional polarizing elements. Therefore, it is speculated that boric acid crosslinking can be used to protect (stabilize) the hydroxyl groups of polyvinyl alcohol in polarizing element 1. Furthermore, it is speculated that, especially when the dichroic pigment contained in polarizing element 1 is iodine (described later), by including an appropriate amount of potassium in polarizing element 1, the iodide ions, which are opposite ions, can be stabilized in polarizing element 1. Therefore, it is believed that when the boron and potassium contents are within the ranges described above, it is easier to more effectively suppress the polyolefination of the PVA-based resin constituting polarizing element 1.

[0063] The transmittance Ty of polarizing element 1 is preferably 38.8% or more, more preferably 40.4% or more, even more preferably 40.7% or more, and preferably 44.8% or less, more preferably 43.2% or less, and even more preferably 43.0% or less. If the transmittance Ty is greater than 44.8%, the optical properties of polarizing element 1 may deteriorate significantly, such as turning red at high temperatures (sometimes referred to as reddening). If the transmittance Ty is less than 38.8%, the polyolefination of PVA-based resin is more likely to occur at high temperatures, leading to greater deterioration of the optical properties of polarizing element 1.

[0064] The transmittance Ty of polarizing element 1 can be determined by measuring the Y value after visibility correction using a 2-degree field of view (C light source) as specified in JIS Z8701-1982. As described in the embodiments described later, the transmittance Ty can be easily measured, for example, using a spectrophotometer (model: V7100) manufactured by Nippon Spectrophotometer Co., Ltd.

[0065] The thickness of polarizing element 1 is preferably 3 μm or more, more preferably 4 μm or more, even more preferably 5 μm or more, and preferably 35 μm or less, more preferably 30 μm or less, and even more preferably 25 μm or less. By making the thickness of polarizing element 1 35 μm or less, it is easy to suppress the decrease in the optical properties of polarizing element 1 due to the polyolefination of PVA-based resin under high temperature conditions. By making the thickness of polarizing element 1 3 μm or more, it is easy to obtain polarizing element 1 with the desired optical properties.

[0066] PVA-based resin layers can be formed using PVA-based resins obtained by saponifying polyvinyl acetate-based resins. Examples of polyvinyl acetate-based resins include polyvinyl acetate as a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate with other monomers that can be copolymerized therewith. Examples of other monomers that can be copolymerized include unsaturated carboxylic acids, olefins such as ethylene, vinyl ethers, and unsaturated sulfonic acids.

[0067] The degree of saponification of the PVA-based resin is preferably 85 mol% or more, more preferably 90 mol% or more, and even more preferably 99 mol% or more and 100 mol% or less. The degree of polymerization of the PVA-based resin is, for example, 1000 or more and 10000 or less, preferably 1500 or more and 5000 or less. The PVA-based resin can be modified, for example, it can be aldehyde-modified polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc.

[0068] Examples of dichroic pigments that are adsorbed and oriented in a PVA-based resin layer include iodine or dichroic dyes. Iodine is preferred as a dichroic pigment.

[0069] The polarizing layer constituting the polarizing element 1 can be, for example, a polarizing layer formed as follows: using a polyvinyl alcohol-based resin film (hereinafter sometimes referred to as "PVA-based resin film") that forms a PVA-based resin layer, dyeing the PVA-based resin film with a dichroic dye, and then uniaxially stretching it; or by coating a substrate film with a coating liquid containing a PVA-based resin to obtain a laminated film with a coating layer forming a PVA-based resin layer on the substrate film, dyeing the coating layer with a dichroic dye, and then uniaxially stretching the laminated film.

[0070] The polarizing layer can be used directly as polarizing element 1, or two or more polarizing layers can be bonded together using an adhesive layer to serve as polarizing element 1. When two or more polarizing layers are stacked, it is preferable to stack them in a manner that makes the absorption axes of the polarizing layers parallel to each other.

[0071] (Method for manufacturing polarization layer)

[0072] There is no particular limitation on the manufacturing method of the polarizing layer constituting the polarizing element 1. Typical methods for manufacturing the polarizing layer include a method of producing a pre-wound PVA-based resin film by stretching, dyeing, cross-linking, etc. (hereinafter referred to as "manufacturing method 1"); and a method that includes stretching a laminated film formed by coating a coating liquid containing PVA-based resin onto a substrate film to form a coating layer (hereinafter referred to as "manufacturing method 2").

[0073] Manufacturing method 1 may include: a step of uniaxially stretching a PVA-based resin film, a step of adsorbing the dichroic pigment by dyeing the PVA-based resin film with a dichroic pigment such as iodine, a step of treating the PVA-based resin film with the adsorbed dichroic pigment with a boric acid aqueous solution, and a step of washing with water after treatment with the boric acid aqueous solution.

[0074] The boron and potassium content in the polarization layer can be controlled by adjusting the concentrations of boron-producing substances such as boric acid, borates, and boron compounds like borax, as well as the concentrations of potassium-producing substances such as potassium halides like potassium iodide, in any of the treatment baths during the swelling, dyeing, crosslinking, stretching, and washing processes, along with the treatment temperature and time of each of these baths. In particular, during the crosslinking and stretching processes, the boron content can be easily adjusted to a desired range by adjusting the concentration of the boron-producing substances. Furthermore, from the viewpoint of being able to dissolve or adsorb boron and potassium from the PVA-based resin film after considering the amount of boron and potassium-producing substances used in the dyeing, crosslinking, or stretching processes, the washing process allows for easy adjustment of the boron and potassium content to a desired range.

[0075] The swelling process involves immersing a PVA-based resin film in a swelling bath. This process removes surface contaminants and adhesives from the PVA-based resin film and suppresses uneven dyeing by causing the film to swell. The swelling bath typically uses a water-based medium, such as water, distilled water, or pure water. Surfactants, alcohols, etc., can be appropriately added to the swelling bath using conventional methods. Furthermore, from the viewpoint of controlling the potassium content in the polarizing layer, potassium iodide can be used in the swelling bath. In this case, the potassium iodide content in the swelling bath is preferably 1.5% by weight or less, more preferably 1.0% by weight or less, and even more preferably 0.5% by weight or less.

[0076] The temperature of the swelling bath is preferably 10–60°C, more preferably 15–45°C, and even more preferably 18–30°C. Regarding the immersion time in the swelling bath, since the degree of swelling of the PVA-based resin film is affected by the temperature of the swelling bath, it cannot be fixed indefinitely; however, it is preferably 5–300 seconds, more preferably 10–200 seconds, and even more preferably 20–100 seconds. The swelling process can be performed only once or multiple times as needed.

[0077] The dyeing process involves immersing a PVA-based resin film in a dyeing bath, which allows dichroic pigments to be adsorbed and oriented on the PVA-based resin film. When the dichroic pigment is iodine, the dyeing bath is preferably an iodine solution. The iodine solution is typically an aqueous iodine solution containing iodine and an iodide as a dissolving agent. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is suitable from the viewpoint of controlling the potassium content in the polarizing layer.

[0078] In the staining bath, the concentration of the dichroic pigment is preferably 0.01 to 1% by weight, more preferably 0.02 to 0.5% by weight. In the staining bath, the concentration of the iodide is preferably 0.01 to 10% by weight, more preferably 0.05 to 5% by weight, and even more preferably 0.1 to 3% by weight.

[0079] The temperature of the dyeing bath is preferably 10–50°C, more preferably 15–45°C, and even more preferably 18–30°C. Regarding the immersion time in the dyeing bath, since the degree of dyeing of the PVA-based resin film is affected by the temperature of the dyeing bath, it cannot be fixed in general; however, it is preferably 10–300 seconds, more preferably 20–240 seconds. The dyeing process can be performed only once or multiple times as needed.

[0080] The crosslinking process involves immersing a PVA-based resin film, which has been dyed in the dyeing process, in a treatment bath (crosslinking bath) containing a boron compound. The PVA resin in the film undergoes crosslinking due to the boron compound, and the dichroic pigment is adsorbed onto this crosslinked structure. Examples of boron compounds include boric acid, borates, and borax. The crosslinking bath is generally an aqueous solution; however, it can also be a mixture of an organic solvent miscible with water and water. From the viewpoint of controlling the potassium content in the polarizing layer, the crosslinking bath preferably contains potassium iodide.

[0081] In the crosslinking bath, the concentration of the boron compound is preferably 1 to 15% by weight, more preferably 1.5 to 10% by weight, and even more preferably 2 to 5% by weight. Furthermore, when the crosslinking bath contains potassium iodide, the concentration of potassium iodide in the crosslinking bath is preferably 1 to 15% by weight, more preferably 1.5 to 10% by weight, and even more preferably 2 to 5% by weight.

[0082] The temperature of the crosslinking bath is preferably 20–70°C, more preferably 30–60°C. Regarding the immersion time in the crosslinking bath, since the degree of crosslinking of the PVA resin in the PVA-based resin film is affected by the temperature of the crosslinking bath, it cannot be fixed in general; however, it is preferably 5–300 seconds, more preferably 10–200 seconds. The crosslinking process can be performed only once, or multiple times as needed.

[0083] The stretching process is a process in which a PVA-based resin film is stretched at least in one direction at a specified ratio. Generally, the PVA-based resin film is uniaxially stretched along the transport direction (length direction). There are no particular restrictions on the stretching method; either wet stretching or dry stretching can be used. The stretching process can be performed once or multiple times as needed. The stretching process can be performed at any stage of the polarizing layer manufacturing process.

[0084] The treatment bath (stretching bath) in the wet stretching process can typically be water, or a solution of an organic solvent miscible with water and water. From the viewpoint of controlling the potassium content in the polarizing layer, the stretching bath preferably contains potassium iodide. When potassium iodide is used in the stretching bath, its concentration is preferably 1 to 15% by weight, more preferably 2 to 10% by weight, and even more preferably 3 to 6% by weight. Furthermore, from the viewpoint of suppressing film breakage during stretching, the treatment bath (stretching bath) may contain a boron compound. In this case, the concentration of the boron compound in the stretching bath is preferably 1 to 15% by weight, more preferably 1.5 to 10% by weight, and even more preferably 2 to 5% by weight.

[0085] The temperature of the stretching bath is preferably 25–80°C, more preferably 40–75°C, and even more preferably 50–70°C. Regarding the immersion time in the stretching bath, since the degree of stretching of the PVA-based resin film is affected by the temperature of the stretching bath, it cannot be fixed indefinitely; however, it is preferably 10–800 seconds, more preferably 30–500 seconds. It should be noted that the stretching treatment in the wet stretching method can be performed together with any one or more of the following processing steps: swelling, dyeing, crosslinking, and washing.

[0086] Examples of dry stretching methods include inter-roll stretching, heated roll stretching, and compression stretching. It should be noted that in dry stretching methods, the stretching process can be performed during the drying process.

[0087] The total stretch ratio (cumulative stretch ratio) applied to the PVA-based resin film can be appropriately set according to the purpose, but it is preferably 2 to 7 times, more preferably 3 to 6.8 times, and even more preferably 3.5 to 6.5 times.

[0088] The washing process involves immersing the PVA-based resin film in a washing bath to remove foreign matter remaining on the surface of the PVA-based resin film. The washing bath typically uses a water-based medium, such as water, distilled water, or pure water. Furthermore, from the viewpoint of controlling the potassium content in the polarizing layer, it is preferable that the washing bath contains potassium iodide. In this case, the concentration of potassium iodide in the washing bath is preferably 1 to 10% by weight, more preferably 1.5 to 4% by weight, and even more preferably 1.8 to 3.8% by weight.

[0089] The temperature of the washing bath is preferably 5–50°C, more preferably 10–40°C, and even more preferably 15–30°C. Regarding the immersion time in the washing bath, since the degree of washing of the PVA resin film is affected by the temperature of the washing bath, it cannot be fixed in general; however, it is preferably 1–100 seconds, more preferably 2–50 seconds, and even more preferably 3–20 seconds. The washing process can be performed only once or multiple times as needed.

[0090] The drying process involves drying the PVA-based resin film that has been washed in the washing process to obtain the polarizing layer. Drying can be carried out using any suitable method, such as natural drying, forced air drying, or heat drying.

[0091] Manufacturing method 2 may include: a step of coating a coating solution containing the above-mentioned PVA-based resin onto a substrate film; a step of uniaxially stretching the resulting laminated film; a step of adsorbing dichroic pigments by dyeing the coating layer of the uniaxially stretched laminated film with dichroic pigments; a step of treating the laminated film with adsorbed dichroic pigments with a boric acid aqueous solution; and a step of washing with water after treatment with the boric acid aqueous solution. The substrate film used to form the polarizing layer can be used as a transparent protective film for a polarizing plate. The substrate film can be peeled off from the polarizing layer as needed.

[0092] (Polarizing plate)

[0093] Figure 2 This is a schematic cross-sectional view illustrating the polarizing plate of this embodiment. The polarizing plate 2 has a polarizing element 1 and a transparent protective film 21. The transparent protective film 21 is provided on one or both sides of the polarizing element 1, but preferably as shown below. Figure 2 As shown, it is disposed on both sides. The polarizing plate 2 may have an adhesive layer (not shown) for bonding the polarizing element 1 to the transparent protective film 21. The adhesive layer is usually in direct contact with the polarizing element 1 and the transparent protective film 21.

[0094] (Transparent protective film)

[0095] The transparent protective film 21 can be a single-layer structure or a multi-layer structure. The transparent protective film can be a single-layer structure with its own optical function, or a multi-layer structure having at least one optically functional layer. From an optical point of view, a thin transparent protective film 21 is preferred; however, if it is too thin, its strength decreases and its processability deteriorates. The thickness of the transparent protective film 21 is, for example, 5 μm or more, preferably 10 μm or more, more preferably 15 μm or more, and, for example, 100 μm or less, preferably 80 μm or less, more preferably 70 μm or less.

[0096] The transparent protective film 21 can be a cellulose acylated film, a polycarbonate resin film, a film containing cyclic olefin resins such as norbornene, a (meth)acrylic polymer film, or a film containing polyester resins such as polyethylene terephthalate. When the polarizing element 1 has transparent protective films 21 on both sides and the polarizing element 1 is bonded to the transparent protective films 21 using a water-based adhesive such as an adhesive containing PVA resin, from the viewpoint of moisture permeability, it is preferable that at least one transparent protective film 21 included in the polarizing plate 2 is a cellulose acylated film or a (meth)acrylic polymer film, with a cellulose acylated film being preferred.

[0097] The polarizer 2 may include at least one transparent protective film 21 that has a phase difference function for purposes such as viewing angle compensation. In this case, the film constituting the transparent protective film 21 may have a phase difference function itself, or the transparent protective film 21 may have a layer without a phase difference function and a phase difference layer (a layer with a phase difference function). When the transparent protective film 21 has a phase difference layer, it may be configured as a laminate of a layer without a phase difference function and a phase difference layer, and these layers may be laminated together using an adhesive layer.

[0098] (Adhesive layer)

[0099] The adhesive used to form the adhesive layer for bonding the polarizing element 1 to the transparent protective film 2l can be any suitable adhesive. Water-based adhesives, solvent-based adhesives, and active energy radiation-cured adhesives can be used, but water-based adhesives are preferred. From the viewpoint of improving heat resistance, the adhesive layer preferably contains at least one urea compound selected from urea, urea derivatives, thiourea, and thiourea derivatives.

[0100] The thickness of the adhesive layer can be set to any appropriate value. For example, it can be set in such a way that an adhesive layer with the desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm or more, and more preferably 7 μm or less, more preferably 5 μm or less, further preferably 2 μm or less, and most preferably 1 μm or less.

[0101] (Water-based adhesive)

[0102] Any suitable water-based adhesive can be used as the water-based adhesive. Among these, a water-based adhesive containing PVA-based resin (PVA-based adhesive) is preferred. Regarding the average degree of polymerization of the PVA-based resin contained in the water-based adhesive, from an adhesiveness perspective, it is preferably 100 or more and 5500 or less, more preferably 1000 or more and 4500 or less. Regarding the average degree of saponification, from an adhesiveness perspective, it is preferably 85 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less.

[0103] As a PVA-based resin contained in a water-based adhesive, a resin containing acetyl groups is preferred. This is because the PVA-based resin layer exhibits excellent adhesion and durability to the transparent protective film. For example, a PVA-based resin containing acetyl groups can be obtained by reacting a PVA-based resin with a diene using any method. The degree of acetyl group modification in the PVA-based resin containing acetyl groups is typically 0.1 mol% or more, preferably 0.1 mol% or more and 20 mol% or less. The content of PVA-based resin in the water-based adhesive is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 15% by mass or less, more preferably 10% by mass or less.

[0104] Water-based adhesives may contain crosslinking agents. Well-known crosslinking agents can be used. Examples include water-soluble epoxy compounds, dialdehydes, and isocyanates.

[0105] When the PVA resin is a PVA resin containing acetyl groups, the crosslinking agent is preferably any one of glyoxal, glyoxylate, and hydroxymethyl melamine, more preferably any one of glyoxal and glyoxylate, and even more preferably glyoxal.

[0106] Aqueous adhesives may contain organic solvents. From the perspective of miscibility with water, the organic solvent is preferably an alcohol, more preferably at least one of methanol and ethanol, and even more preferably methanol. Among the urea compounds that may be contained in the adhesive layer, there are compounds with low solubility relative to water but sufficient solubility relative to alcohols. In this case, one preferred method is to dissolve the urea compound in an alcohol to prepare an alcohol solution of the urea compound, and then add the alcohol solution of the urea compound to an aqueous solution of PVA-based resin to prepare the aqueous adhesive.

[0107] When the aqueous adhesive contains methanol, the methanol content in the aqueous adhesive is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and preferably 70% by mass or less, more preferably 60% by mass or less. By keeping the methanol content at 10% by mass or more, it is easier to suppress the polyolefination of the PVA-based resin constituting the polarizing element under high-temperature conditions. By keeping the methanol content at 70% by mass or less, the deterioration of the color tone of the polarizing element can be suppressed. The methanol content in the aqueous adhesive is the proportion of methanol when the aqueous adhesive is set to 100% by mass.

[0108] (Active energy radiation curing adhesive)

[0109] Reactive energy radiation-cured adhesives are adhesives that cure upon exposure to reactive energy radiation such as ultraviolet rays. Examples include adhesives containing polymerizable compounds and photopolymerization initiators, adhesives containing photoreactive resins, and adhesive resins containing photoreactive crosslinking agents. Examples of polymerizable compounds include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, as well as oligomers derived from these monomers. Examples of photopolymerization initiators include compounds that generate reactive species such as neutral free radicals, anionic free radicals, and cationic free radicals upon exposure to reactive energy radiation such as ultraviolet rays.

[0110] (Urea compounds)

[0111] When the adhesive layer contains a urea-based compound, it contains at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives. As a method for containing a urea-based compound in the adhesive layer, a method for containing a urea-based compound in the aforementioned adhesive can be cited. When the adhesive used to bond the polarizing element 1 to the transparent protective film 21 contains a urea-based compound, during the process of forming the adhesive layer by applying the adhesive and then drying it, a portion of the urea-based compound can move from the adhesive to the polarizing element 1, etc. That is, the polarizing element 1 can contain a urea-based compound. Urea-based compounds include water-soluble compounds and poorly water-soluble compounds; either type of urea-based compound can be used. When using a poorly water-soluble urea-based compound in an aqueous adhesive, it is preferable to study a dispersion method for the urea-based compound in a manner that does not cause an increase in haze during the formation of the adhesive layer.

[0112] When the adhesive is an aqueous adhesive containing PVA-based resin and urea-based compound, the content of urea-based compound relative to 100% by mass of PVA-based resin is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, and preferably 400% by mass or less, more preferably 200% by mass or less, and even more preferably 100% by mass or less.

[0113] (Urea derivatives)

[0114] Urea derivatives are compounds in which at least one of the four hydrogen atoms of a urea molecule is substituted with a substituent. In this case, there are no particular restrictions on the substituent, but it is preferred that it contains a carbon atom and a substituent selected from at least one of hydrogen and oxygen atoms.

[0115] Specific examples of urea derivatives, in terms of monosubstituted ureas, include methylurea, ethylurea, propylurea, butylurea, isobutylurea, N-octadecylurea, 2-hydroxyethylurea, hydroxyurea, acetylurea, allylurea, 2-propynylurea, cyclohexylurea, phenylurea, 3-hydroxyphenylurea, (4-methoxyphenyl)urea, benzylurea, benzoylurea, o-tolylurea, and p-tolylurea.

[0116] Examples of disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-di(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-di(4-methoxyphenyl)urea, and 1-acetyl-3-methylurea.

[0117] Examples of tetrasubstituted ureas include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, and 1,3-dimethoxy-1,3-dimethylurea.

[0118] (Thiocarbamide derivatives)

[0119] Thiourea derivatives are compounds in which at least one of the four hydrogen atoms of a thiourea molecule is substituted with a substituent. In this case, there are no particular restrictions on the substituent, however, substituents containing a carbon atom and at least one selected from hydrogen and oxygen atoms are preferred.

[0120] Specific examples of thiourea derivatives, in terms of monosubstituted thioureas, include N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, (2-methoxyethyl)thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea.

[0121] Examples of disubstituted thioureas include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, and N-allyl-N'-(2-hydroxyethyl)thiourea.

[0122] Examples of trisubstituted thioureas include trimethylthiourea, and examples of tetrasubstituted thioureas include tetramethylthiourea and 1,1,3,3-tetraethylthiourea.

[0123] When the polarizer 2 is used in the image display device with interlayer filling described later, from the viewpoint of effectively suppressing the decrease in transmittance Ty under high-temperature conditions, the urea compound is preferably a urea derivative or a thiourea derivative, more preferably a urea derivative. Among the urea derivatives, monosubstituted urea or disubstituted urea is preferred, more preferably a monosubstituted urea. The disubstituted urea can be any of a 1,1-substituted urea and a 1,3-substituted urea, more preferably a 1,3-substituted urea.

[0124] (Urea compounds contain a layer)

[0125] The adhesive layer used to bond the polarizing element 1 to the transparent protective film 21, as described above, can be a urea-based compound containing layer. In the polarizing plate 2, from the viewpoint of improving the heat resistance of the polarizing plate 2, other layers besides the adhesive layer can also be configured as urea-based compound containing layers.

[0126] In recent years, in response to the demand for thinner polarizing plates, polarizing plates with a transparent protective film 21 on only one side of the polarizing element 1 have been developed. In this type of polarizing plate, for the purpose of improving physical strength, a curing layer can be laminated on the side of the polarizing element 1 that does not have the transparent protective film 21. This curing layer can be a urea-based compound containing layer. The curing layer can be formed from a curable composition containing an organic solvent, or from an aqueous solution of an active energy ray curable polymer composition (Japanese Patent Application Laid-Open No. 2017-075986, paragraphs

[0020] to

[0042] ). When the curing layer is a urea-based compound containing layer, a mixture containing a water-soluble urea-based compound in the above-mentioned aqueous solution can be used to form the curing layer.

[0127] (Manufacturing method of polarizing plate)

[0128] The manufacturing method of the polarizing plate 2 includes a lamination process of stacking the polarizing element 1 and the transparent protective film 21, and may further include a moisture content adjustment process. The lamination process may be a process of stacking the polarizing element 1 and the transparent protective film 21 using an adhesive.

[0129] The moisture content adjustment process is a process of adjusting the moisture content of polarization element 1. For example, it can be a process of adjusting the moisture content of polarization element 1 to be above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C. The moisture content of polarization element 1 can also be below the equilibrium moisture content of 50% relative humidity at 20°C, or below the equilibrium moisture content of 45% relative humidity at 20°C.

[0130] As a method to confirm that the moisture content of polarizing element 1 is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C, the following methods can be cited: storing the polarizing element in an environment adjusted to the above temperature and relative humidity range for a certain period of time and confirming that there is no change in mass; or pre-calculating the equilibrium moisture content of the polarizing element in an environment adjusted to the above temperature and relative humidity range and comparing the moisture content of the polarizing element with the pre-calculated equilibrium moisture content. If the polarizing element is stored for a certain period of time and its mass does not change, it can be considered that the moisture content in the storage environment has reached equilibrium.

[0131] There are no particular limitations on the method for adjusting the moisture content of the polarizing element 1 to a balance moisture content of 30% or higher at a temperature of 20°C and a balance moisture content of 80% or lower at a temperature of 20°C. For example, methods such as storing the polarizing element in an environment adjusted to the above temperature and relative humidity range for 10 minutes or more and 3 hours or less, or performing heat treatment at 30°C or higher and 90°C or lower can be cited.

[0132] In the moisture content adjustment process, the moisture content of the polarizing plate 2 can be adjusted to a level above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 80% relative humidity at 20°C. Alternatively, the moisture content of the polarizing plate 2 can be below the equilibrium moisture content of 50% relative humidity at 20°C or below the equilibrium moisture content of 45% relative humidity at 20°C. The method for adjusting the moisture content of the polarizing plate 2 can be the same as the method for adjusting the moisture content of the polarizing element 1 described above.

[0133] There is no restriction on the order of the moisture content adjustment process and the lamination process; the moisture content adjustment process and the lamination process can also be performed in parallel.

[0134] (Image display device)

[0135] Polarizing plate 2 is used in various image display devices such as liquid crystal display devices and organic EL display devices. In image display devices where the polarizing plate is configured with layers other than an air layer on both sides, specifically solid layers such as adhesive layers (hereinafter sometimes referred to as "interlayer filling configuration"), the transmittance Ty of the polarizing element tends to decrease at high temperatures. In image display devices using the polarizing plate 2 of this embodiment, even with an interlayer filling configuration, the decrease in transmittance Ty of the polarizing element 1 at high temperatures can be suppressed. Image display devices using polarizing plate 2 can also suppress the decrease in polarization degree Py and hue ab of the polarizing element 1 at high temperatures.

[0136] Examples of solid layers include adhesive layers or bonding agent layers. When the solid layer is an adhesive layer, it is preferable to use an adhesive layer formed with a UV-curable adhesive.

[0137] Regarding an image display device, an example can be illustrated by having an image display unit, a first adhesive layer laminated to the viewing side surface of the image display unit, and a polarizer laminated to the viewing side surface of the first adhesive layer. This image display device may further include a second adhesive layer laminated to the viewing side surface of the polarizer and a transparent component laminated to the surface of the second adhesive layer. Preferably, the image display device has an interlayer filling configuration where the polarizer and the image display unit are bonded using the first adhesive layer, and the polarizer and the transparent component are bonded using the second adhesive layer.

[0138] The polarizing plate and the image display unit are not limited to being bonded using the first adhesive layer; they can also be bonded using an adhesive layer. Similarly, the polarizing plate and the transparent component are not limited to being bonded using the second adhesive layer; they can also be bonded using an adhesive layer. Examples of adhesive layers described above include the adhesive layers described above.

[0139] (Image display unit)

[0140] Examples of image display units include liquid crystal units (LCDs) and organic EL units (OLEDs). A liquid crystal unit can be any of the following: a reflective liquid crystal unit that utilizes external light, a transmissive liquid crystal unit that utilizes light from a light source such as a backlight, or a semi-transmissive / semi-reflective liquid crystal unit that utilizes both external light and light from a light source. When the liquid crystal unit utilizes light from a light source, the image display device (liquid crystal display device) also provides a polarizing plate on the side of the image display unit (liquid crystal unit) opposite to the viewing side, and further provides a light source. The polarizing plate on the light source side is preferably bonded to the liquid crystal unit via a suitable bonding layer. As for the driving method of the liquid crystal unit, any type of driving method can be used, such as VA mode, IPS mode, TN mode, STN mode, or π-type bending orientation.

[0141] As an organic EL unit, an organic EL unit in which a transparent electrode, an organic light-emitting layer, and a metal electrode are sequentially stacked on a transparent substrate to form a light emitter (organic electroluminescent body) can be appropriately used. The organic light-emitting layer is a stack of various organic thin films, such as a stack of a hole injection layer containing a triphenylamine derivative and a light-emitting layer containing a fluorescent organic solid such as anthracene, a stack of these light-emitting layers and an electron injection layer containing a perylene derivative, or a stack of a hole injection layer, a light-emitting layer, and an electron injection layer, etc.

[0142] (The bonding of the image display unit and the polarizing plate)

[0143] In the bonding of the image display unit and the polarizing plate, a first adhesive layer (adhesive sheet) can be appropriately used. From an operability perspective, it is preferable to bond the image display unit to the polarizing plate, to which the first adhesive layer is attached. The attachment of the first adhesive layer to the polarizing plate can be performed in a suitable manner. Examples include preparing an adhesive solution containing 10% by mass or more and 40% by mass or a combination thereof of a base polymer dissolved or dispersed in a solvent containing a suitable solvent such as toluene or ethyl acetate, and directly attaching it to the polarizing plate using a suitable spreading method such as casting or coating; or transferring (printing) the first adhesive layer onto the polarizing plate after it has been formed on a spacer.

[0144] (First adhesive layer, second adhesive layer)

[0145] The first adhesive layer and the second adhesive layer (hereinafter sometimes collectively referred to as "adhesive layers") can each be formed independently of one or more layers, but preferably of one layer. The adhesive layer can be composed of an adhesive composition with (meth)acrylic resin, rubber resin, urethane resin, ester resin, silicone resin, or polyvinyl ether resin as the main component. Among these, an adhesive composition with (meth)acrylic resin as the base polymer, which has excellent transparency, weather resistance, and heat resistance, is suitable. The adhesive composition can also be of the active energy radiation curing type or the thermosetting type.

[0146] The (meth)acrylic resin (base polymer) used in the adhesive composition can suitably be a polymer or copolymer with one or more (meth)acrylate monomers such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. The base polymer is preferably a copolymer copolymerized with a polar monomer. Examples of polar monomers include (meth)acrylate compounds, 2-hydroxypropyl (meth)acrylate compounds, hydroxyethyl (meth)acrylate compounds, (meth)acrylamide compounds, N,N-dimethylaminoethyl (meth)acrylate compounds, and glycidyl (meth)acrylate compounds, which have carboxyl, hydroxyl, amide, amino, or epoxy groups.

[0147] The adhesive composition may contain only the aforementioned base polymer, but typically also contains a crosslinking agent. Examples of crosslinking agents include metal ions that are divalent or higher metal ions and form a carboxylic acid metal salt therebetween with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxide compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among these, polyisocyanate compounds are preferred.

[0148] The active energy radiation-curable adhesive composition possesses the property of curing upon irradiation with active energy radiation such as ultraviolet rays or electron beams. It also exhibits adhesiveness even before irradiation, enabling it to adhere tightly to substrates such as films, and the ability to adjust the adhesion force through curing upon irradiation. The active energy radiation-curable adhesive composition is preferably ultraviolet-curable. In addition to containing a base polymer and a crosslinking agent, the active energy radiation-curable adhesive composition also contains an active energy radiation-polymerizable compound. Depending on the requirements, it may contain photopolymerization initiators, photosensitizers, etc.

[0149] The adhesive composition may contain additives such as microparticles, beads (resin beads, glass beads, etc.) for imparting light scattering properties, glass fibers, resins other than the base polymer, tackifiers, fillers (metal powders, other inorganic powders, etc.), antioxidants, ultraviolet absorbers, dyes, pigments, colorants, defoamers, corrosion inhibitors, and photopolymerization initiators.

[0150] The adhesive layer can be formed by applying an organic solvent dilution of the adhesive composition described above to the surface of a substrate film, an image display unit, or a polarizing plate and then drying it. The substrate film is typically a thermoplastic resin film; a typical example is a spacer that has undergone a release treatment. The spacer can be, for example, a component for which a release treatment, such as silicone treatment, is applied to the surface of a film containing resins such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, or polyarylate, is performed to form the adhesive layer.

[0151] An adhesive composition can be directly applied to the release surface of the spacer to form an adhesive layer, and this adhesive layer with the spacer is then laminated onto the surface of the polarizing plate. Alternatively, an adhesive composition can be directly applied to the surface of the polarizing plate to form an adhesive layer, and the spacer can be laminated onto the outer surface of the adhesive layer.

[0152] When the adhesive layer is applied to the surface of the polarizing plate, it is preferable to perform surface activation treatments such as plasma treatment or corona treatment on the bonding surface of the polarizing plate and / or the bonding surface of the adhesive layer, and more preferably to perform corona treatment.

[0153] Alternatively, an adhesive sheet can be prepared by coating an adhesive composition onto the second spacer to form an adhesive layer, and then stacking the spacer on the formed adhesive layer. The adhesive layer with the spacer after the spacer is peeled off from the adhesive sheet is then stacked on the polarizing plate. The second spacer uses a component with weaker adhesion to the adhesive layer and easier to peel off compared to the spacer.

[0154] The thickness of the adhesive layer is not particularly limited, but it is preferably 1 μm or more, more preferably 3 μm or more, and may also be 20 μm or more. In addition, it is preferably 100 μm or less, more preferably 50 μm or less.

[0155] (Transparent component)

[0156] Examples of transparent components that can be disposed on the viewing side of an image display device include a front panel (window layer) and a touch panel. For the front panel, a transparent sheet with appropriate mechanical strength and thickness is used. Examples of such transparent sheets include transparent resin sheets made of polyimide-based resins, acrylic resins, polycarbonate resins, or glass sheets. Functional layers such as anti-reflective layers can also be laminated on the viewing side of the transparent sheet. Furthermore, when the transparent sheet is a transparent resin sheet, a hard coating can be laminated to improve physical strength, and a low-permeability layer can be laminated to reduce moisture permeability. Examples of touch panels include various types such as resistive film, capacitive, optical, and ultrasonic touch panels, as well as glass sheets and transparent resin sheets with touch sensor functionality. When using a capacitive touch panel as the transparent component, it is preferable to provide a transparent sheet made of glass or a transparent resin sheet on the viewing side relative to the touch panel.

[0157] (The bonding of the polarizing plate to the transparent component)

[0158] In bonding the polarizing plate to the transparent component, a second adhesive layer or an active energy radiation-cured adhesive can be appropriately used. When using a second adhesive layer, it can be attached in a suitable manner. As a specific attachment method, the attachment method using the first adhesive layer described above in the bonding of the image display unit to the polarizing plate can be cited as an example.

[0159] When using an active energy ray-cured adhesive, to prevent the adhesive solution from spreading before curing, a suitable method can be used as follows: a dam material is set up to surround the periphery of the image display panel; a transparent component is placed on the dam material; and the adhesive solution is injected. After the adhesive solution is injected, alignment and degassing are performed as needed, and then the adhesive solution is cured by irradiation with active energy rays.

[0160] (Adhesive layer)

[0161] The bonding layer is an adhesive layer or a bonding agent layer. In addition to the adhesive layer and bonding agent layer (first adhesive layer and second adhesive layer) described above, adhesive layers formed using known adhesives and bonding agent layers formed using known adhesives can also be cited as adhesive layers and bonding agent layers formed using known adhesives.

[0162] Example

[0163] The present invention will now be specifically described based on embodiments. The materials, reagents, quantities, proportions, and operations described below can be appropriately modified without departing from the spirit of the invention. Therefore, the present invention is not limited or restricted by the following embodiments.

[0164] [Determination and Evaluation Methods]

[0165] (1) Measurement of the thickness of the polarization element

[0166] The thickness of the polarization element was measured using a digital micrometer "MH-15M" manufactured by Nikon Corporation.

[0167] (2) Measurement of the transmittance, polarization degree, and hue of the polarizing plate with visibility correction monomer.

[0168] The transmittance of the visible-corrected monomer, the degree of polarization corrected by the visible-corrected polarization, and the hue of the polarizing plate were measured using a spectrophotometer with an integrating sphere (V7100 manufactured by Nippon Spectrophotometer Co., Ltd., 2-degree field of view; C-light source). Since the transparent protective film used to manufacture the polarizing plate described later and the adhesive layer formed using the polarizing plate adhesive are both colorless and transparent, the transmittance of the visible-corrected monomer, the degree of polarization corrected by the visible-corrected polarization, and the hue measured on the polarizing plate can be considered as the transmittance of the visible-corrected monomer, the degree of polarization corrected by the visible-corrected polarization, and the hue of the polarizing element.

[0169] (3) Determination of boron content

[0170] The boron content in the polarizing element was determined using the following steps. First, 0.2 g of the polarizing element was dissolved in 200 g of a 1.9% (w / w) mannitol aqueous solution. Then, the resulting aqueous solution was titrated with a 1 mol / L sodium hydroxide aqueous solution. The boron content in the polarizing element was calculated by comparing the amount of sodium hydroxide solution required for neutralization with a standard curve.

[0171] (4) Determination of staining degree

[0172] Figure 3 (a) and (b) are illustrative diagrams illustrating the steps used to determine staining degree. Figure 3 (a) is a diagram illustrating the method of cutting out the sample 20t for measurement from the polarizing plate 20 prepared using the steps described later. Figure 3 (b) is a diagram illustrating the Raman spectrometry measurement of sample 20t, with the cut surface of polarization element 10t magnified. Figure 4 This is an explanatory diagram used to illustrate the method of calculating the integrated intensity distribution from Raman spectra.

[0173] (Preparation of samples for determination)

[0174] Using an ultrathin slicer (LEICA RM2255, manufactured by LEICA), such as Figure 3As shown in (a), a polarizing plate 20 is cut along a plane formed by the absorption axis direction (tension direction) 101 of the polarizing element 10 and the thickness direction 100 of the polarizing element 10, and a measurement sample 20t with a length d (thickness of the cut plate) in a direction orthogonal to this plane is produced. Figure 3 (a)

[0175] (Raman spectrophotometry)

[0176] The apparatus and measurement conditions used in Raman spectrophotometry are shown below.

[0177] • Apparatus: Laser Raman spectrophotometer (NRS-5100, manufactured by Nippon Spectrophotometer Co., Ltd.)

[0178] • Excitation wavelength: 532.23nm

[0179] • Grating: 18001 / mm

[0180] • Objective lens: 100x visible

[0181] • Measurement interval: 1μm

[0182] Raman spectroscopy is performed on the polarization element 10t portion of the cut surface of sample 20t (the surface formed by cutting with an ultramicrotome). Measurement points p, spaced 1 μm apart, are set along the thickness direction (surface direction of the cut surface) 100 of the polarization element 10t. A laser L is incident with its polarization plane parallel to the absorption axis direction (stretch direction) 101 of the polarization element 10t and perpendicular to the cut surface of sample 20t. An analyzer is positioned on the side of sample 20t opposite to the incident surface of laser L (the rear side of sample 20t). The polarization plane of the analyzer is set to be parallel to the polarization plane of laser L.

[0183] In any Raman spectrum obtained by measuring the polarization element of the sample made from the polarizing plate described later, the value is found at 108 cm⁻¹. -1 Nearby observations corresponding to I3 - The peak, in addition, at 158cm -1 Nearby observations corresponding to I5 - The peak.

[0184] (I3 - and I5 - (Calculation of integral intensity distribution)

[0185] Because the main absorber in the visible light region (380nm~780nm) is polyiodine (I3) - I5 - The complex formed by polyiodine and polyvinyl alcohol (polyiodine-PVA complex) can be obtained by measuring I3.- and I5 - The Raman intensity was compared to the effective amount of iodine that affected the observation. The specific calculation steps are shown below.

[0186] like Figure 4 As shown, the wavenumber 80 cm⁻¹ in the Raman spectrum is used. -1 The value at 130cm -1 The straight line at the value is used to approximate the baseline of the Raman spectrum as a straight line. Figure 4 The line ef in the approximate Raman spectrum is used as the Raman intensity. The slope of the baseline during the Raman spectrum measurement is corrected by using the distance (intensity) relative to the approximate line ef as the Raman intensity, and the wavenumber 80cm is calculated. -1 ~130cm -1 The integral area of ​​the interval ( Figure 4 In the middle, the area enclosed by the straight line ef and the diagonal portion of the Raman spectrum from e to f is denoted as I3. - The integral strength.

[0187] In addition, such as Figure 4 As shown, the wavenumber 130 cm⁻¹ in the Raman spectrum is used. -1 The value at 180cm and the wave number -1 The straight line at the value is used to approximate the baseline of the Raman spectrum as a straight line. Figure 4 The approximate line fg is used as the Raman intensity. The slope of the baseline during Raman spectroscopy is corrected by using the distance (intensity) relative to the approximate line fg as the Raman intensity, and the wavenumber 130cm is calculated. -1 ~180cm -1 The integral area of ​​the interval ( Figure 4 In the middle, the area enclosed by the straight line fg and the slanted portion of the Raman spectrum from f to g is denoted as I5. - The integral strength.

[0188] By measuring I3 at each measurement point p - The integral intensity and I5 - The sum of the integrated intensities is plotted relative to each measurement point p to obtain the integrated intensity distribution along the thickness direction of the polarizing element 10t. In this integrated intensity distribution, the integrated areas of the three regions distinguished by dividing the polarizing element 10t into three equal parts along the thickness direction are calculated and set as the staining degree of the three regions containing the polarizing element in the polarizing plate of the measurement sample 10t.

[0189] (5) High temperature durability test

[0190] (Preparation of the evaluation sample)

[0191] Referring to the embodiment disclosed in Japanese Patent Application Publication No. 2018-025765, an acrylic adhesive (manufactured by LINTEC Corporation) was applied to both sides of a polarizing plate prepared using the steps described later, thereby forming an adhesive layer with a thickness of 25 μm. The polarizing plate with adhesive layers formed on both sides was cut to a size of 50 mm × 100 mm, and alkali-free glass (trade name "EAGLE XG", manufactured by Coming Corporation) was laminated onto the surface of each adhesive layer to produce an evaluation sample. During the preparation of the evaluation sample, before laminating the alkali-free glass, in order to adjust the moisture content of the polarizing element, the polarizing plate with adhesive layers formed on both sides was stored for 72 hours at a temperature of 20°C and a relative humidity of 40%. Since no change was observed in the quality of the polarizing plates with adhesive layers formed on both sides of the polarizing plate produced by the steps described later, when the storage time was 66 hours, 69 hours, and 72 hours, the equilibrium moisture content of the polarizing element, the polarizing plate, and the polarizing plate with adhesive layers can all be regarded as the same as the equilibrium moisture content at a temperature of 20°C and a relative humidity of 40% for a 72-hour storage environment.

[0192] (High-temperature durability test)

[0193] The evaluation results obtained above were obtained using samples at a temperature of 50℃ and a pressure of 5 kgf / cm. 2 (490.3 kPa) Autoclave treatment was performed for 1 hour. Next, after placing the evaluation sample in an environment of 23°C and 55% relative humidity for 24 hours, the visibility-corrected monomer transmittance, visibility-corrected polarization degree, and hue of the polarizer were measured and set as initial values. Then, a high-temperature durability test was conducted, in which the evaluation sample was stored in a high-temperature environment of 115°C for 144 hours, and the visibility-corrected monomer transmittance, visibility-corrected polarization degree, and hue of the polarizer after the high-temperature durability test were measured.

[0194] Based on the initial values ​​of the visibility-corrected monomer transmittance, visibility-corrected polarization degree, and hue of the polarizing plate, and the measured values ​​after the high-temperature durability test, the changes in the visibility-corrected monomer transmittance, visibility-corrected polarization degree, and hue of the polarizing plate are calculated. The changes in visibility-corrected monomer transmittance ΔTy and visibility-corrected polarization degree ΔPy are calculated by subtracting the measured values ​​after the high-temperature durability test from the initial values. Furthermore, the change in hue Δab is calculated using the following formula.

[0195] Δab={(a1-a2) 2 +(b1-b2) 2} 1 / 2

[0196] Here, a1 and b1 are the initial values ​​of the hue, and a2 and b2 are the measured values ​​of the hue after the high-temperature durability test.

[0197] [Fabrication of polarization element A]

[0198] (Preparation of PVA solution for adhesives)

[0199] 50g of a modified PVA resin containing acetyl groups (manufactured by Mitsubishi Chemical Corporation: Gohsenx Z-410) was dissolved in 950g of pure water, heated at 90°C for 2 hours, and then cooled to room temperature to obtain a PVA solution for adhesives.

[0200] (Fabrication of polarization layer 1)

[0201] A 20 μm thick PVA-based resin film was immersed in pure water at 21.5 °C for 79 seconds, followed by immersion in an aqueous solution containing 1.0 mM iodine as a dichroic pigment at 23 °C for 160 seconds (potassium iodide / boric acid / water weight ratio 2 / 2 / 100). Then, it was immersed in an aqueous solution with a potassium iodide / boric acid / water weight ratio of 2.5 / 4 / 100 at 60.8 °C for 76 seconds. Next, it was immersed in an aqueous solution with a potassium iodide / boric acid / water weight ratio of 3 / 5.5 / 100 at 45 °C for 11 seconds. Finally, it was dried at 38 °C to obtain a 6.5 μm thick polarizing layer 1 where iodine is adsorbed and oriented on the PVA-based resin film (PVA-based resin layer). Stretching was mainly performed during the iodine dyeing and boric acid treatment processes, with a total stretching ratio of 5.85 times.

[0202] (Fabrication of polarization layer 2)

[0203] A 20 μm thick PVA-based resin film was immersed in pure water at 21.5 °C for 79 seconds, followed by immersion in an aqueous solution containing 1.0 mM iodine as a dichroic pigment at 23 °C for 142 seconds (potassium iodide / boric acid / water weight ratio 2 / 2 / 100). Then, it was immersed in an aqueous solution with a potassium iodide / boric acid / water weight ratio of 2.5 / 4 / 100 at 60.8 °C for 76 seconds. Next, it was immersed in an aqueous solution with a potassium iodide / boric acid / water weight ratio of 3 / 5.5 / 100 at 45 °C for 11 seconds. Finally, it was dried at 38 °C to obtain a 6.5 μm thick polarizing layer 2 where iodine is adsorbed and oriented on the PVA-based resin film (PVA-based resin layer). Stretching was mainly performed during the iodine dyeing and boric acid treatment processes, with a total stretching ratio of 5.85 times.

[0204] (Fabrication of polarization element A)

[0205] Using the PVA adhesive solution obtained above, polarizing layer 1, polarizing layer 2, and polarizing layer 1 were sequentially stacked and dried at 23°C and 55% relative humidity to fabricate a polarizing element A (thickness: 19.5 μm) with a layer structure of polarizing layer 1 / polarizing layer 2 / polarizing layer 1. In polarizing element A, the absorption axes of polarizing layer 1, polarizing layer 2, and polarizing layer 1 are parallel. The boron content in polarizing element A is 4.62% by mass.

[0206] [Fabrication of polarizing element B]

[0207] A 45 μm thick PVA-based resin film was immersed in pure water at 21.5 °C for 79 seconds, followed by immersion in an aqueous solution containing 1.0 mM iodine as a dichroic pigment at 23 °C for 151 seconds (potassium iodide / boric acid / water weight ratio 2 / 2 / 100). Then, it was immersed in an aqueous solution with a potassium iodide / boric acid / water weight ratio of 2.5 / 4 / 100 at 60.8 °C for 76 seconds. Next, it was immersed in an aqueous solution with a potassium iodide / boric acid / water weight ratio of 3 / 5.5 / 100 at 45 °C for 11 seconds. Finally, it was dried at 38 °C to obtain a 18 μm thick polarizing element B with iodine adsorbed and oriented on the PVA-based resin film (PVA-based resin layer). Stretching was mainly performed during the iodine dyeing and boric acid treatment processes, with a total stretching ratio of 5.85 times.

[0208] The boron content in polarizing element B is 4.62% by mass.

[0209] [Preparation of Polarizing Plate 1]

[0210] (Preparation of adhesive for polarizing plates)

[0211] An adhesive for a polarizing plate is obtained by combining a PVA solution for adhesive prepared using the steps described in the fabrication of polarizing element A with a content of 3.0% by mass of modified PVA resin containing acetyl groups, 35% by mass of methanol, and 0.5% by mass of urea.

[0212] (Making of a transparent protective film)

[0213] A commercially available cellulose acylated membrane, TJ40UL (manufactured by Fujifilm Corporation, thickness: 40 μm), was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) maintained at 55°C for 2 minutes, followed by water washing. Then, the membrane was immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25°C for 30 seconds, and subsequently washed with running water for 30 seconds to neutralize the membrane. This process was repeated three times using an air knife for dehydration. After dehydration, the membrane was dried in a drying zone at 70°C for 15 seconds to obtain a saponified cellulose acylated membrane, which was used as a transparent protective film.

[0214] (Fabrication of Polarizing Plate 1)

[0215] Using a roller laminator, a transparent protective film was bonded to both sides of polarizing element A using the polarizing adhesive obtained above, and then dried at 80°C for 3 minutes to obtain polarizing plate 1. The polarizing adhesive between polarizing element A and the transparent protective film was prepared such that the thickness of each adhesive layer after drying was 100 nm. The staining degree of polarizing element A was measured using polarizing plate 1, and a high-temperature durability test was performed. The results are shown in Table 1. In polarizing element A, the region with the lowest staining degree is the region located in the center of the thickness direction of polarizing element A.

[0216] [Fabrication of Polarizing Plate 2]

[0217] Except that polarizing element B is used instead of polarizing element A, polarizing plate 2 is fabricated using the same steps as polarizing plate 1. The staining degree of polarizing element B is measured using polarizing plate 2, and a high-temperature durability test is performed. The results are shown in Table 1. In polarizing element B, the region with the lowest staining degree is located in the central region along the thickness direction of polarizing element B.

[0218] [Table 1]

[0219] Polarizing plate 1 Polarizing plate 2 polarization element Polarizing element A Polarizing element B Coloration degree S1 3.33 3.10 Staining degree S2 2.75 3.02 S2 / S1 0.83 0.97 Region with staining degree S2 central central High temperature durability test △Ty 1.3% 2.8% △Py 0.06% 0.13% △ab 4.0NBS 8.4NBS

[0220] Explanation of reference numerals in the attached figures

[0221] 1. Polarizing element, 2. Polarizing plate, 10 and 10t polarizing elements, 11-13 regions, 20 and 20t polarizing plates, 21. Transparent protective film, 210 and 210t transparent protective film, L laser, P measurement point, 100 thickness direction, 101 absorption axis direction (tension direction).

Claims

1. A polarizing element, which is formed by the adsorption and orientation of dichroic pigments in a polyvinyl alcohol-based resin layer, wherein the color intensity of the region with the highest color intensity among three regions divided by tripling the polarizing element in the thickness direction is set as S1, and the color intensity of the region with the lowest color intensity is set as S2, satisfies the following relationship (1): 0≤S2 / S1≤0.95 (1) The region with the lowest staining intensity among the three regions is the region located in the center along the thickness direction. The staining intensity is determined by the wavenumber 80 cm⁻¹ of the Raman spectrum. -1 ~180cm -1 The integral intensity over the interval is calculated.

2. The polarization element according to claim 1, wherein, The polarization element contains boron. The boron content in the polarization element is 4.0% by mass or more and 8.0% by mass or less.

3. The polarization element according to claim 1 or 2, wherein, The dichroic pigment is iodine.

4. A polarizing plate having a polarizing element and a transparent protective film as described in any one of claims 1 to 3.

5. The polarizing plate according to claim 4, further comprising an adhesive layer for bonding the polarizing element to the transparent protective film. The adhesive layer is a layer obtained by curing a water-based adhesive.

6. The polarizing plate according to claim 5, wherein, The aqueous adhesive contains methanol. The methanol content in the aqueous adhesive is 10% by mass or more and 70% by mass or less.

7. The polarizing plate according to claim 5 or 6, wherein, The water-based adhesive also includes polyvinyl alcohol resin.

8. The polarizing plate according to claim 5 or 6, wherein, The thickness of the adhesive layer is greater than 0.01 μm and less than 7 μm.

9. The polarizing plate according to any one of claims 4 to 6, wherein, The polarizing plate is used in an image display device. In the image display device, a solid layer is provided in contact with both sides of the polarizing plate.

10. An image display device comprising an image display unit, a first adhesive layer laminated on the observation-side surface of the image display unit, and a polarizing plate laminated on the observation-side surface of the first adhesive layer, as described in any one of claims 4 to 9.

11. The image display device according to claim 10, further comprising a second adhesive layer laminated on the observation-side surface of the polarizing plate, and a transparent component laminated on the observation-side surface of the second adhesive layer.

12. The image display device according to claim 11, wherein, The transparent component is a glass plate or a transparent resin plate.

13. The image display device according to claim 11, wherein, The transparent component is a touch panel.

Citation Information

Patent Citations

  • Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment

    JP1999174417A

  • Polarizing plate and image display device, and manufacturing method of those

    JP2014102353A

  • Polarizing plate with adhesive layer and manufacturing method of the same, active energy ray curable polymer composition used for the manufacture, and liquid crystal display

    JP2017075986A

  • Optical laminate

    JP2018025765A

  • Polarizing plate and manufacturing method thereof

    CN101960340A